Implementasi Program DESTANA sebagai Upaya Mitigasi dan Kesiapsiagaan Bencana di Desa Mojotengah, Kedu, Temanggung - Sulistriani Sulistriani; Dwi Agus Melani; Muhammad Fahmi Nurhadi; Rahma Febrian; Viona Dwi Puspitasari; Zahida Akmila Dina; Anindya Putri Andini; Fadhlan Surya Ardhika; Prayoga Restu Samudra; Anggita Banowati; Septiko Aji; Firman Kurniawan (Universitas Negeri Semarang, 2026)
Mojotengah Village, Kedu Subdistrict, Temanggung Regency, has a high potential for disasters, including floods, landslides, droughts, and tornadoes. This study aims to describe the implementation of the Disaster Resilient Village (DESTANA) program to mitigate and enhance the village community's preparedness against potential disasters. The method used was Participatory Rural Appraisal (PRA), involving village officials, the community, students from the community service program, and the Temanggung Regency Disaster Management Agency (BPBD). The results of the study show that the DESTANA program increased community capacity by forming the “Mojo Tangguh” organization, preparing disaster management documents, conducting participatory risk mapping, and implementing evacuation simulations. This program not only improved technical preparedness but also fostered a culture of disaster awareness among the community. Although there are still limitations in evacuation facilities, shelters, and the need for ongoing training, the synergy between the community, government, universities, and related institutions has strengthened the resilience of Mojotengah Village in facing disasters. Thus, DESTANA can serve as a model for community-based mitigation integrated with sustainable village development.